Taxonomic placement of Millettia occidentalis (Leguminosae, Papilionoideae), a rare liana from the Amazon Basin - Camargo, Rodrigo A.; Tozzi, Ana Maria G.a. (Phytotaxa, 2016)
A new combination is proposed for Millettia occidentalis, a rare liana endemic to a small locality of the Amazon Basin, in Brazil. Morphology and geographic distribution supports its transfer to Deguelia and a specimen at IAN is designated as lectotype. Validation in Deguelia is needed for use in impending floristic treatments, as well as to promote conservation and new field efforts. It occurs in “terra firme” forests (non-flooded), on high lands and appears to be very rare range-wide, based on documented occurrences. Description, illustration, distribution map, some ecological notes and a preliminary evaluation of its conservation assessment are provided.